High Blood Glucose Levels Correlate with Tumor Malignancy in Colorectal Cancer Patients - Cui, Ge (Med Sci Monit, 2015)
BACKGROUND: Research shows that type 2 diabetes mellitus (T2DM) affects the risk and prognosis of colorectal cancer (CRC). Here, we conducted a retrospective study to investigate whether the clinicopathological features of CRC patients correlate with their blood glucose levels. MATERIAL/METHODS: We enrolled 391 CRC patients hospitalized in our center between 2008 and 2013. Data of their first fasting plasma glucose (FPG) and 2-h postprandial glucose (2hPPG) level after admission, their clinicopathological features, and survival were collected. The correlations between blood glucose level and clinicopathological features were analyzed by Pearson chi-square analysis. Patient survival was analyzed by Kaplan-Meier and Cox-regression analysis. RESULTS: There were 116 out of the 391 CRC patients who had high blood glucose level (H-G group, 29.67%), among which 58 (14.83%), 18 (4.60%), and 40 (10.23%) were diabetes mellitus (DM), impaired glucose tolerance (IGT), and impaired fasting glucose (IFG), respectively, while 275 (70.33%) patients had normal glucose level (N-G group). Compared with the N-G group, patients in the H-G group had larger tumor diameters and lower tumor differentiation (p<0.05). A higher ratio of patients in the H-G group also had more advanced TNM staging and more ulcerative CRC gross type (p<0.05). No significant difference was observed in patient overall survival among different glucose groups. No effect of insulin therapy on CRC development and patient survival was observed. CONCLUSIONS: Blood glucose level in CRC patients correlates significantly with local tumor malignancy, but no significant effect on distant metastasis and patient overall survival was observed.